Little bear's special wish - Lobel, Gillian; Hansen, Gaby (Little Tiger Great britain, 2003)
Little Brown Bear has a very special wish. He wants to find the best birthday present in the whole world for his mummy. And then he sees it - a glittering, magical star. Perfect! But how does one little bear catch a star from high in the sky and make his dearest wish come true?